EVALUATION OF TRAVEL AGENT’S RESERVATION CONTRIBUTION ON THE OCCUPANCY IN PELANGI BALI HOTEL AND SPA - Ni Luh Putu Sri Artini; Budi Susanto; I Ketut Sutama (Politeknik Negeri Bali, 2018)
Offline and online travel agent has important role to improve the hotel room occupancy in order to fill monthly and yearly budget. The purpose of this study is to determine the evaluation of offline and online travel agent’s reservation contribution on the occupancy in Pelangi Bali Hotel and Spa. This research is a descriptive statistic research which is presented by statistic tables and data collected by interviewing the Sales Executive at Pelangi Bali Hotel and Spa, observation and documentation. The result showed that the contribution of offline and online travel agent in the last 3 years is unstable each month, this is can showed from the average of offline travel agent contribution on 2015 is 24,05%, on 2016 is 29,93%, and on 2017 is 32,95%, while the average of online travel agent contribution on 2015 is 40,24%, on 2016 is 30,54%, and on 2017 is 40,03%. The comparation between contribution of offline and online travel agent in the last 3 years is not significant, however between reservation from offline and online travel agent, contribution from online travel agent is always increasingly every year. That showed online travel agent contribution gives enhance to the room occupancy more than offline travel agent contribution.